Oxidation behavior of 9Cr-4.5Al ODS steel in 600 °C supercritical water and the effect of pre-oxidation. (1st April 2020) - Xu, Shuai; Long, Fei; Persaud, Suraj Y.; Guo, Ning; Yao, Zhongwen; Daymond, Mark R.; Gao, Wenhua; Zhang, Lefu; Zhou, Zhangjian
Highlights: The oxidation behavior of a 9Cr-4.5Al ODS steel in 600℃ supercritical water was investigated. A thin alumina layer formed by pre-oxide treatment can well protect the sample at the beginning of the corrosion test. The existence of M23 C6 (M = Cr, Fe) in the 9Cr-4.5Al ODS steel is detrimental to oxidation resistance. All samples follow the "available space model" oxidation mechanism as exposure time is extended. Abstract: The oxidation behavior of a 9Cr-4.5Al ODS steel in 600℃ supercritical water with 200 ppb dissolved oxygen was investigated with and without a pre-oxidation heat treatment. In general, results suggest that all samples follow the "available space model" oxidation mechanism as exposure time is extended. Based on the microstructural analysis, it is found that a thin alumina layer formed by pre-oxidation treatment is initially protective up to approximately 100 h. However, this passive film becomes ineffective due to the existence of M23 C6 (M = Cr, Fe) and the insufficient content of Al or/and Cr in the steel.